Joint analysis of left ventricular expression and circulating plasma levels of Omentin after myocardial ischemia - Louis A. Saddic; Sarah M. Nicoloro; Olga T. Gupta; Michael P. Czech; Joshua Gorham; Stanton K. Shernan; Christine E. Seidman; Jon G. Seidman; Sary F. Aranki; Simon C. Body; Timothy P. Fitzgibbons; Jochen D. Muehlschlegel (Cardiovascular Diabetology, 2017)
Abstract Background Omentin-1, also known as Intelectin-1 (ITLN1), is an adipokine with plasma levels associated with diabetes, obesity, and coronary artery disease. Recent studies suggest that ITLN1 can mitigate myocardial ischemic injury but the expression of ITLN1 in the heart itself has not been well characterized. The purpose of this study is to discern the relationship between the expression pattern of ITLN1 RNA in the human heart and the level of circulating ITLN1 protein in plasma from the same patients following myocardial ischemia. Methods A large cohort of patients (n = 140) undergoing elective cardiac surgery for aortic valve replacement were enrolled in this study. Plasma and left ventricular biopsy samples were taken at the beginning of cardiopulmonary bypass and after an average of 82 min of ischemic cross clamp time. The localization of ITLN1 in epicardial adipose tissue (EAT) was also further characterized with immunoassays and cell fate transition studies. Results mRNA expression of ITLN1 decreases in left ventricular tissue after acute ischemia in human patients (mean difference 280.48, p = 0.001) whereas plasma protein levels of ITLN1 increase (mean difference 5.24, p < 0.001). Immunohistochemistry localized ITLN1 to the mesothelium or visceral pericardium of EAT. Epithelial to mesenchymal transition in mesothelial cells leads to a downregulation of ITLN1 expression. Conclusions Myocardial injury leads to a decrease in ITLN1 expression in the heart and a corresponding increase in plasma levels. These changes may in part be due to an epithelial to mesenchymal transition of the cells that express ITLN1 following ischemia. Trial Registration Clinicaltrials.gov ID: NCT00985049